Highly oxidized low-density lipoprotein does not facilitate platelet aggregation. Issue 10 (October 2020) - Miyazaki, Akari; Uehara, Takeshi; Usami, Yoko; Ishimine, Nau; Sugano, Mitsutoshi; Tozuka, Minoru
Objective: This study aimed to examine whether oxidized low-density lipoprotein (oxLDL) facilitates platelet aggregation, which is one cause for development of cardiovascular disease. Methods: The susceptibility of platelets to aggregation was monitored by light transmittance aggregometry and a laser light scattering method using low-density lipoprotein (LDL) and oxLDL as agonists. β-thromboglobulin (β-TG) levels released from platelets were also measured after incubation with or without oxLDL. Results: Platelet aggregation was suppressed by oxLDL as estimated by maximum light transmission. Additionally, adenosine diphosphate-induced further aggregation was slightly reduced by the presence of oxLDL. Aggregation levels of a low number of platelets, which was determined by the laser light scattering method, were lower upon addition of oxLDL compared with unoxidized LDL. After a short time of incubation, oxLDL increased secreted β-TG levels in platelet-rich plasma. However, further incubation with oxLDL caused relatively lower secreted β-TG levels compared with incubation with unoxidized LDL. This fluctuation was not due to β-TG degradation by oxLDL. Conclusions: Levels of oxLDL in vitro weakly activate platelets at an early stage, but then inhibit platelet function, such as aggregation and β-TG secretion.